1994
DOI: 10.1101/gad.8.12.1400
|View full text |Cite
|
Sign up to set email alerts
|

The global transcriptional regulators, SSN6 and TUP1, play distinct roles in the establishment of a repressive chromatin structure.

Abstract: Repression of a-cell specific gene expression in yeast ~ cells requires MATch2 and MCM1, as well as two global repressors, SSN6 and TUP1. Previous studies demonstrated that nucleosomes positioned adjacent to the a2/MCM1 operator in c~ cells directly contribute to repression. To investigate the possibility that SSN6 and TUP1 provide a link between MAT~2/MCM1 and neighboring histones, nucleosome locations were examined in ssn6 and t u p l ot cells. In both cases, nucleosome positions downstream of the operator w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
162
0
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(177 citation statements)
references
References 66 publications
13
162
0
2
Order By: Relevance
“…Previous studies revealed that the α2/Mcm1 repressor, in conjunction with the Ssn6-Tup1 corepressor and the Isw2 complexes establishes an array of positioned nucleosomes to form a repressive chromatin structure [15,17,20,21,[28][29][30]32]. Our results imply that the positioned nucleosomes in the repressive chromatin function to limit the accessibility of at least a certain class of activators in vivo, therefore supporting the idea that nucleosome positioning plays a vital role in repression by α2/Mcm1.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Previous studies revealed that the α2/Mcm1 repressor, in conjunction with the Ssn6-Tup1 corepressor and the Isw2 complexes establishes an array of positioned nucleosomes to form a repressive chromatin structure [15,17,20,21,[28][29][30]32]. Our results imply that the positioned nucleosomes in the repressive chromatin function to limit the accessibility of at least a certain class of activators in vivo, therefore supporting the idea that nucleosome positioning plays a vital role in repression by α2/Mcm1.…”
Section: Discussionsupporting
confidence: 86%
“…The hypersensitive site was detectable in a cells, in which nucleosomes were not positioned, but it was strongly diminished in α cells, indicating that Hap1 binding is severely limited at the dyad in the positioned nucleosome IV. Similar results for Hap1 binding were obtained for TALS-UAS1b (lanes [19][20][21][22][23][24] and -UAS1c (lanes [28][29][30][31][32][33], in which the UAS1 site was located in the peripheral region of the positioned nucleosome IV; that is, the hypersensitive site is present in a cells, but absent in α cells. It should be noted that the location of UAS1 in TALSUASc is shifted to 5 bp exterior to the nucleosome edge, as compared to that in TALS-UAS1b.…”
Section: Effect Of the Uas1 Locations In A Positioned Nucleosome On Hsupporting
confidence: 80%
See 3 more Smart Citations